2022
DOI: 10.3390/ma15062251
|View full text |Cite
|
Sign up to set email alerts
|

Si-Doped HfO2-Based Ferroelectric Tunnel Junctions with a Composite Energy Barrier for Non-Volatile Memory Applications

Abstract: Ferroelectric tunnel junctions (FTJs) have attracted attention as devices for advanced memory applications owing to their high operating speed, low operating energy, and excellent scalability. In particular, hafnia ferroelectric materials are very promising because of their high remanent polarization (below 10 nm) and high compatibility with complementary metal-oxide-semiconductor (CMOS) processes. In this study, a Si-doped HfO2-based FTJ device with a metal-ferroelectric-insulator-semiconductor (MFIS) structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…5, the reliability characteristics of the FTJ device are verified, and the HfO x -based FTJ continuously raises the need for memory window maintenance and high endurance. 53 Fig. 5(a) shows the endurance characteristic in terms of switching cycles from ±6 to ±7 V, increasing the amplitude by 0.2 V. Previous reports have indicated that the lower the voltage, the higher the endurance, but the lower the peak value of 2P r , the lower is the memory window.…”
Section: Resultsmentioning
confidence: 97%
“…5, the reliability characteristics of the FTJ device are verified, and the HfO x -based FTJ continuously raises the need for memory window maintenance and high endurance. 53 Fig. 5(a) shows the endurance characteristic in terms of switching cycles from ±6 to ±7 V, increasing the amplitude by 0.2 V. Previous reports have indicated that the lower the voltage, the higher the endurance, but the lower the peak value of 2P r , the lower is the memory window.…”
Section: Resultsmentioning
confidence: 97%
“…The general techniques for implementing the various resistance states of the FTJ are amplitude or pulse width adjustments of the programming pulse [ 19 , 29 ]. Figure 3 a depicts the measurement process, which gradually increases the amplitude of the programming pulse to change the resistance state.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the asymmetric potential barrier, a state in which a significant amount of current flows due to low energy barriers to tunneling is called a low-resistance state (LRS); in contrast, a state in which less current flows due to high energy barriers to tunneling is called a high-resistance state (HRS). The tunnelling electro-resistance effect is a phrase for describing these two electrical resistance states [ 24 ]. In this study, the HRS and LRS of the manufactured FTJ device were verified using a semiconductor parameter analyzer ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%